Carotid Artery Stenting and Concomitant Coronary Artery Bypass Grafting or other Cardiac Surgical Procedures - Paolo Nardi; Guglielmo Saitto; Marco Russo; Giovanni Ruvolo (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
Editorial Almost 8% to 14% of patients undergoing coronary artery bypass grafting (CABG) have significant internal carotid artery stenosis requiring treatment [1]. A carotid artery disease, especially when a high-risk plaque is present, represents an important risk factor for stroke after cardiac surgery, in particular after CABG. For these reasons carotid endarterectomy (CEA) before or concomitantly to cardiac surgery [1-4] has been proposed, but these procedures have been reported to carry a 10% to 12% cumulative risk of death, stroke, or myocardial infarction (MI) [5]. To date, no consensus exists for the best approach for the management of combined severe carotidand coronary or other than coronary cardiac disease. Carotid artery stenting (CAS) has been evolving in these last decades to be a valid alternative to traditional carotid endarterectomy for CABG patients in consideration of their high-risk profile [6-7]. CAS followed by CABG after several weeks has been proposed as a staged approach, but the increased risk of myocardial infarction in the interval [8-9] may represent a major limitation. Moreover, the need for dual antiplatelet aggregation therapy for 3 to 4 weeks after CAS increases the risk of bleeding if surgery is urgently required in the meantime [9].